ESTABLISHING A PAEDIATRIC FORMULARY TO STANDARDISE PRESCRIBING IN CHILDREN. Issue 6 (18th May 2015) - Khan, Farrah; Garrett, Sarah; Patel, Priya; Hamilton-Farrell, Martin
Abstract : Aim: To create a paediatric formulary that incorporates standardised guidelines and enables consistent prescribing for children across all legacy sites of the largest teaching NHS trust in the UK. Method: The merger of six local hospitals into one large Trust proved challenging for paediatrics from a medicines management perspective. Prior to merger the three main legacy sites each had individual formularies, primarily for adults. The merged Trust now had the greatest number (135) of paediatric beds for an NHS Trust in England. With beds spread across the various sites, and each legacy site using different prescribing guidelines, it posed a significant risk, particularly as staff moved regularly between sites. To standardise prescribing for children across the new Trust, a paediatric pharmacist was recruited to the inter-disciplinary Formulary Committee, whose initial remit was to create a convergent adult formulary using BNF Formulary Complete. The paediatric pharmacist was tasked with producing a unified paediatric formulary, using BNFC Formulary Complete. A robust business case highlighting the urgent need to create a unified formulary secured funding for the project. From the outset, the Formulary Committee met regularly to review progress and to set targets. The formulary was developed in chapters, one at a time, following the BNF format. First a spread-sheet was created for each chapter; all drugs currently on formulary at any of the sites were coloured green. The spreadsheet was then populated with specialist prescribing tips and guidelines (local and national). This presented the team with an ideal opportunity to review all paediatric guidelines being used across the legacy sites, and merge, update or discard as necessary. The spreadsheet was then sent to consultants and stakeholders with a specialist interest in that chapter for review and comments. Results: Once all comments had been collated, the content of the spreadsheet, including locally specific prescribing information, was transferred to BNFC Formulary Complete. Following a final accuracy check, the chapter was made live. Rapid access to all relevant guidelines was enabled via hyperlinks; thereby creating a one-stop reference point to support safe prescribing in children. Conclusion: Three chapters have been completed so far. The main issue has been to distinguish between guidelines that apply to secondary or tertiary care, or both. There has been excellent engagement from the paediatricians, and their comments have been extremely positive. In addition, the paediatric Pharmacy team has contributed significantly to enable the update of the guidelines. The whole project has been steered by the Formulary Committee through setting key milestones and maintaining an overview of the assignment. The aim is to continue to make each chapter live as it is completed; reviewing the whole formulary within a two year time-frame. This staggered approach to going live has enabled the smooth implementation of the formulary, with minimal problems.